Hermynia Zur Muhlen the guises of socialist fiction - Wallace, Ailsa, 1977- (Oxford modern languages and literature monographs., 2009)
Zur Muhlen saw literature primarily as a political tool and used popular forms of literature to convey her ideas to a wide audience. This book examines her prose fiction against the backdrop of her life and the turbulent times she lived in - the Weimar Republic and exile from the Third Reich.